Forages - Maass, Brigitte L.; Hanson, Jean; Robertson, L.D.; Kerridge, Peter C.; Abd El Moneim, A.M. (Cambridge University Press, 1997)
Forages are usually associated with grasslands, but they also occur and are used widely on roadsides, in fallow areas, and as crop residues. In temperate areas livestock is grazed on domesticated forages. In the tropics livestock use native grasslands (Africa, Australia), naturalized grasslands (tropical America, Asia), or grasslands improved with selected wild species (tropical America). The worldwide exchange of forage germplasm has involved relatively few accessions of some widely adapted species, and the need exists to increase the diversity of these cultivated forages. Topics of discussion include botany and distribution, germplasm conservation and use, collections of CIAT ILRI and ICARDA, tropical forages, legumes, browse and grasses, temperate and tropical highland legumes and temperate and tropical highland legumes and grasses. Prospects and limitations are examined at the end of the paper.